PENGARUH PERSONAL SELLING TERHADAP KEPUTUSAN BERKUNJUNG DI JENDELA ALAM - Prasetyo, Adhitya Aji; Ridwanudin, Oce (Universitas Pendidikan Indonesia, 2016)
One of the areas in Indonesia which has many tourism potentials is West Java. It has so attracted many touristsfor its beauty in natural and cultural resources. Bandung is the capital of West Java. It has so many tourists'attractions. One of the tourist’s attractions is “Jendela Alam,